The Political Conflict Between the Leaders of South Sudan 1965-1983 - Coeur , Ali (Al-Adab Journal, 2024)
The research shed light on the personal and tribal differences and individual ambitions that existed between the leaders of the South inside and outside Sudan. Confusion prevailed among the leadership of the Sanu Party abroad following William Deng’s defection and the Sudanese government’s acceptance of his peace proposals. Because of these differences in viewpoints, the leaders of the South took up arms. confronting each other, even though they all met for the goal of secession. These tribal differences and conflicts resulted in the establishment of several political organizations abroad, which resulted in the formation of several governments that were unable to do much for the people of the South. As for the political conflict that broke out between the leaders of South Sudan at home, It came after the conclusion of the Addis Ababa Agreement in 1972, and the assignment of Abel Alier to head the regional government of the south, as there were many southerners who did not welcome that assignment, led by Joseph Lagu and Clement Mboro, as they felt that their rights had been taken away from them and given to those who did not deserve it.